Teacher´s performance of itinerant teaching in relation to the inclusion of low vision children in elementary education - Dall'Acqua, Maria Júlia Canazza (Paidéia (Ribeirão Preto), 2007)
At a time in which the inclusion of students with special education needs in regular schools has been discussed, it is necessary to develop researches to evaluate the implications of teachers' continued education. In this sense, the objective of investigating aspects related to the needs of two itinerant teachers was established. Theses teachers are participants of a formation program. Such program has the goal to follow-up low vision students. It managed to offer these teachers, who had no specific knowledge in visual disability, elements of this formation, and also to evaluate the nature of evidenced implications along the process from which it was possible to conclude that the visual functions development is constituted by valuable theorical referential, as well as the fact of being regulary at school, talk to the teachers, discuss how to proceed, evaluate the exercises retroactively and help them to plan strategies based on the analysis done. These were the main advantages of acting in a colaborative manner.